1960
DOI: 10.1042/bj0750372
|View full text |Cite
|
Sign up to set email alerts
|

The enzymic condensation of porphobilinogen to porphyrins

Abstract: is no correlation between anticholinesterase activity and effectiveness as reactivator. The ratios (potency as reactivator:reactivity with organophosphates), obtained with different oximes, support the interpretation that attachment to the phosphorylated enzyme during reactivation enhances activity. Possible sites of attachment are discussed. We wish to thank the Department of Scientific and Industrial Research for the special research grant to P. W.S., which has defrayed some of the cost of this work. We are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Preheating of the porphobilinogenase at 700C for 30min destroyed isomerase activity almost completely, resulting in an increase of total uroporphyrin formation (Table 4). These results agree with the findings of Booij & Rimington (1957), Lockwood & Benson (1960), Cornford (1964) and Llambias & Batlle (1970d). Heat inactivation is slightly greater, occurring after shorter time-intervals, when isomerase is heated alone.…”
Section: Incubation Conditions Anaerobicsupporting
confidence: 92%
See 4 more Smart Citations
“…Preheating of the porphobilinogenase at 700C for 30min destroyed isomerase activity almost completely, resulting in an increase of total uroporphyrin formation (Table 4). These results agree with the findings of Booij & Rimington (1957), Lockwood & Benson (1960), Cornford (1964) and Llambias & Batlle (1970d). Heat inactivation is slightly greater, occurring after shorter time-intervals, when isomerase is heated alone.…”
Section: Incubation Conditions Anaerobicsupporting
confidence: 92%
“…It has also been found that 8-aminolaevulate dehydratase, isolated from the same tissue, was firmly bound to a nucleoprotein (Tigier et al 1970). Bogorad (1958a,b), Lockwood & Benson (1960) and Sancovich et al (1969b) have shown that porphobilinogenase and deaminase were as active in the absence of oxygen as in its presence; we have observed that the activity of porphobilinogenase was affected by the presence of air. The yield of uroporphyrinogens was highest under anaerobic conditions, although consumption of substrate was not modified by air, suggesting that some intermediate in the reaction was still being formed, but that this compound, probably some polypyrrolic intermediate (Llambias & Batlle, 1970a), must be in the reduced form to be further enzymically converted into uroporphyrinogens; the presence of air would prevent this reduction (A. M. Stella, V. E. Parera, E. B. C. Llambfas & A. M. del C. Batlle, unpublished work).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations